INTERNALISING THE PRINCIPLE OF FAITH IN TEACHING-LEARNING - Wan Mohamad Nasir; Azlan Jaafar; Nor Zaihana Abdul Rahman; Norlela Yacob, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Islam does not make any distinction between religiousity and secular matters. Muslims as servants and vicegerents of Allah are responsible for continually reaffirming their faith in all their activities. This includes teaching-learning as a principal role of a teacher and it encompasses classroom, laboratory, clinic and community engagement activities. The objective of this paper is to explore the application of the principles of faith in teaching-learning activities in a curriculum that integrates naqli and aqli knowledge. It adopts the qualitative research method involving a review of literature that is related to teaching methodology as well as studying the verses of the Quran and the parables of the hadith on faith. In general, teaching-learning sessions consist of three parts, namely the opening, the engagement with students and the closure. In internalising the principle of faith, teachers must start an activity by professing that Allah is the Most Beneficent and the Most Merciful followed by greeting the students. Subsequently, they need to perform supplication in seeking guidance from Allah so that they can perform their tasks with excellence. When engaging with students, praises such as Alhamdulillah, Subhanallah and Maa sya Allah, as well as Astaghfirullah are reinforcements that can enhance repetition of a behaviour. The closure of a teaching-learning session must reinforce the belief in the superiority of Allah that only He knows best. This approach exemplifies the testimony of faith that Allah is one and continually strengthened in all our endeavours including teaching-learning. The concepts derived from this principle will be disseminated to all lecturers in this Faculty for implementation.